Justifying Sexual Violence and Blaming Victims: A Forensic Discourse Analysis of Suspect Narratives in Indonesian Rape Examination Reports - Ekfindar Diliana; Dina Mariana Br Tarigan; Zem Santo; Santy Monika; Muhammad Saiful Fahmi (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study examines how rape suspects construct discursive legitimacy for their actions through justification and victim-blaming strategies in Indonesian police examination reports (Berita Acara Pemeriksaan—BAP). Using a qualitative forensic linguistic approach, the study analyzes linguistic data derived from a rape suspect’s statements documented in an official BAP from Merauke Regency, Indonesia. The analysis is informed by van Leeuwen’s (2008) theory of legitimation, Ryan’s (1971) concept of victim blaming, and forensic discourse analysis to investigate how language is strategically employed to explain, justify, and normalize criminal behavior. Data were analyzed through identification, categorization, and interpretation of lexical choices, causal constructions, evaluative expressions, and agency representations. The findings reveal three dominant discursive strategies. First, emotional and biological justifications are employed to frame the offense as a consequence of jealousy, anger, and sexual desire rather than deliberate criminal intent. Second, victim-blaming strategies construct the victim’s sexual history and social interactions as factors contributing to the assault. Third, responsibility-shifting strategies minimize perpetrator accountability by foregrounding the victim’s behavior while backgrounding the suspect’s agency. The study contributes theoretically by extending legitimation theory to suspect narratives in Indonesian legal discourse, a largely underexplored area in forensic linguistics. It highlights the significance of language in shaping representations of perpetrators and victims within sexual violence investigations and legal processes.